Conflict between Religions A Study of Modern Approaches in Sῑrah Writing - Muhaimin, Abdul (Journal of Islamic and Religious Studies, 2016)
The world has been changing ever since its creation, yet the pace of change in the last one hundred years or so has been the most rapid ever. The effects of these changes were beyond the limitations of time and region and therefore they directly affected the Muslim world as well. Muslim scholars did not ignore these changes and realized their responsibilities and wrote books of Sīrah which provided guidance in connection with these rapid changes and conditions. This research has highlight an important issue of the conflict between religions, its inception, history and primarily focused on the opinions of the authors of selected books of Sῑrah written in recent past. This research has also elaborated the modern approaches in Sῑrah writing. The study has mainly focused on significant Sῑrah books of three languages i.e. Arabic, English and Urdu. These books include Fiqh Al Sῑrah by Muḥammad Sa’īd Ramaḍān Al Būtī, Fiqh Al Sῑrah by Muḥammad Al Ghazālī, Madnī Mu‘āshrah by Akram Ḍīā Al ‘Umrī, The Life and the Work of the Prophet by Dr. Muḥammad Ḥamīdullāh, The Spirit of Islam by Sayīd Amīr ‘Alī, Muhammad A Biography of Prophet by Karen Armstrong, Sīrah Al Nabī by ‘Allāmah Shiblī Nu’mānī, Aṣaḥ Al Sῑyar by ‘Abdul Raūf Dānāpūrī, Ḍīā Al Nabī by Pīr Muḥammad Karam Shāh, Sīrati Sarwari ‘Alam by Abūl A‘lā Mūdūdī, Raḥmatullil'ālamīn by Qāḍī Muhammad Sulymān Manṣūrpūrī and Muḥammad Rasūlallāh by Sayīd Muḥammad Mīyān.